Concepções acerca da espiritualidade no processo de cuidado em saúde dos profissionais de uma equipe multidisciplinar que atua com pacientes crônicos - Pinto, Bruna Teixeira (Universidade Federal de São Carlos, 2018)
The hospital is a place that covers different phases of the human life cycle, from birth, diagnostic discoveries to proximity to finiteness of life, which favors the pursuit of essential meanings to life and the treatment process itself. Research shows that the inclusion of spirituality in the therapeutic processes can improve the patients’ quality of life as well as stimulate either a faster healing process or confrontation with the diseases. Thus, spirituality has been gaining ground in the academic world, being increasingly present in the triad patient-care in health-support team. This study aimed to identify how health professionals who working in the infectious diseases ward at Américo Brasiliense State Hospital, located in Américo Brasiliense, São Paulo, signify spirituality and how they offer spiritual care to hospitalized patients. This is an observational study with a qualitative approach, was carried out with 25 health professionals. Data collection was conducted through an open interview consisting of two guiding questions: "What does spirituality mean to you?" and "How do you offer spiritual care to hospitalized patients in the ward of infectious-contagious diseases?" examined using thematic content analysis. The results showed that professionals conceptualize spirituality as the connection with the transcendent, sometimes calling it God or superior Being, and perform spiritual care based on their own conception of spirituality, which causes difficulties when the subject, the focus of care, has a concept of spirituality divergent from that of the professional. Both the lack of and the little knowledge of the subject was highlighted as a limiting factor in the approach to the spirituality in the process of health care.
Conceptions about spirituality in the health care process of the professionals of a multidisciplinary team that works with chronic patients
Keywords: Espiritualidade; Doenças crônicas; Equipe de assistência ao paciente; Spirituality; Chronic diseases; Patient care team; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA